ANALISIS PENGARUH TINGKAT INFLASI, NILAI TUKAR USD/RUPIAH, DAN TINGKAT SUKU BUNGA SBI TERHADAP INDEK HARGA SAHAM GABUNGAN - Machmud, Senen; Wijanarko, Bambang Agus (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
This study was conducted to analyze the effect of variable inflation rates, exchange rate of USD / IDR and SBI interest rate on JCI. Research hypothesis: 1.Variabel inflation rate (X1), affect the JCI, 2.Variabel exchange rate of USD / IDR (X2) effect on JCI, 3.Variabel SBI rate (X3) influence the JCI, 4.Variabel inflation (X1), the exchange rate of USD / IDR (X2) and SBI interest rate (X3), simultaneously affect the JCI. The data were analyzed secondary data, time series with the period April 2007 to March 2009. Data collection was obtained by downloading the http://www.idx.co.id/ site, to obtain monthly JCI, and http: // www.bi.go.id/web/id/, to obtain data on inflation, the data exchange rate of USD / IDR and SBI rate. Data processing is intended to measure the relationship of causality (cause-effect), the independent variable or the independent variable, the dependent variable or dependent variable. Appropriate analytical tools for this purpose is a multiple regression analysis. Media processing of data to test the hypothesis of this study using SPSS (Statistical Product and Service Solutions). Regression analysis, concluded that together (simultaneously), all three variables, namely the rate of inflation, exchange rate USD / IDR and rate of SBI rates significantly affect the JCI. In partial significance test variable inflation rate does not affect the JCI, while the variable exchange rate of USD / IDR and SBI interest rate showed significant results with a coefficient of 0.18 and 3.29. Recommendations that can be given is, the investor community should be more selective in choosing stocks that want to have. Macroeconomic variables should be examined carefully in conjunction with the JCI, primarily SBI interest rate, given the impact that a significant and dominant with coefficient of 3.29%. The Government as Regulator, then monetary policy can be taken is to control inflation by targeting low inflation, stabilize the SBI interest rate and stabilize the rupiah exchange rate against the US dollar, given the changes in these variables affect the JCI. Control variables SBI certainly should be preferred for the formulation of monetary policy, given the variables have a significant effect as well as dominant against JCI.